Red velvet seat : women's writings on the first fifty years of cinema - Lant, Antonia; Periz, Ingrid (Verso, 2006)
As viewers, actresses, directors and writers, women have always been central to cinema. However, evidence of their roles has until now remained scant and dispersed, eclipsed by historical opinion written by men. In magisterial scale, Red Velvet Seat restores women's film culture to center stage, using women's written accounts from the beginning of cinema up to 1950. Drawing on fashion and parenting magazines, newspapers and literary journals, memoirs and etiquette guides, and with contributors ranging from Virginia Woolf, Colette, and Rebecca West to psychoanalysts, poets, social reformers, labor organizers, film editors, screen beauties, and race activists, the volume displays the full scope of women's film culture. In each section, editor Antonia Lant with Ingrid Periz provides historical context and links archival accounts to major social and political movements. Comprehensive and absorbing, Red Velvet Seat is an invaluable contribution to the history of cinema.